TURUNNYA SUARA PARTAI PERSATUAN PEMBANGUNAN KABUPATEN JEPARA - Akhsin M; Purwoko .; Fitriyah . (Journal of Politic and Government Studies, 2017)
The general election as the Democratic Party carried out throughout Indonesia including Jepara Jepara is a small town located in the northern part of Central Java with a majority muslim population and the socio-cultural circumstances has spelled out that it was written so as to make the State of the political situation is somewhat different from other areas. Proven PPP which is the Islamic party managed to become a strong party in Jepara. Elections in the postelection reform Jepara always won by the PPP from year to year, but winning the election for PPP in coupled with the number of votes the PPP also getting down at each election. In the current study focused on researching the factors causing the decline of anything from year to year the PPP vote, whereas historically the PPP has a lot of followers and Jepara Regency has socio-cultural islam. In this study, the author uses qualitative research methods are analytical, descriptive, using the technique of purposive sampling techniques the taking of the sample that is where researchers choose informants deemed relevant and knowledgeable which is a representation of the problem being studied. Engineering data retrieval using in-depth interviews with the informant, and secondary data with reference data written, and other data that support. Upon the decline of the PPP vote results is the existence of a multi-party system, the system elections is fickle, and less internal conflict over the activities of the party, the shifting behavior of voters, to political money. The factor that makes the sound of PPP Jepara Regency decreased. Advice that can be given to increase the back the sound of PPP is to ways to improve the cadre recruitment by rekruitment cadres who have the loyalty and spirit of the PPP, in addition diadakanya regular meetings need to be consolidated between the present cadres down to over PPP cadres so as to make the more powerful.